Bombesin‐functionalized water‐soluble gold nanoparticles for targeting prostate cancer. Issue 4 (11th December 2017) - Simpson, Emily J.; Gobbo, Pierangelo; Bononi, Fernanda C.; Murrell, Emily; Workentin, Mark S.; Luyt, Leonard G.
Abstract: Cancer targeting can be used for both tumor diagnosis and therapy. Recently, gold nanoparticles (AuNPs) have found utility in this field as they are very small in size, and thus display an enhanced permeability and retention effect, allowing them to be taken up by tumor cells through "passive targeting." However, this accumulation is non‐specific. Conversely, AuNPs functionalized with targeting entities such as peptides, antibodies, or small molecules can specifically target tumors through interaction with cancer‐specific protein receptors. In this study, targeted AuNPs were developed using an azide‐modified peptide that was able to react with alkyne‐functionalized AuNPs through an interfacial strain‐promoted azide‐alkyne cycloaddition. Small (3 nm) AuNPs were made water‐soluble through PEGylation and functionalized with dibenzocyclooctyne to add the alkyne functionality. For the targeting entity, a pan‐bombesin peptide ([D‐Phe 6, β‐Ala 11, Phe 13, Nle 14 ]bombesin(6–14)) was chosen as it binds to all four receptor subtypes of the gastrin releasing peptide receptor, which is highly expressed in prostate cancer. Prostate cancer (PC‐3) cells were incubated with the targeted AuNPs and studied via transmission electron microscopy. AuNPs conjugated with bombesin showed higher accumulation in PC‐3 cells than either the blocking or control studies. These results suggest that these small, water‐soluble, bombesin‐functionalized AuNPs have potential applications in targeting prostate cancer as diagnostic or therapeutic entities. Abstract : Prostate cancer cells were targeted using bombesin‐functionalized, water‐soluble, gold nanoparticles. The functionalized nanoparticles demonstrated higher accumulation in prostate cancer cells than the non‐targeted control nanoparticles, as determined by transmission electron microscopy (TEM). Therefore, these peptide functionalized nanoparticles have potential application in targeting prostate cancer as diagnostic or therapeutic entities.